Literature Challenges in Digital Platforms, the Wattpad Platform as a Model - Shukur, Harith Yaseen; Ameen, Naaman Th. Mohamad; Awad, Hadyatallah Medhat Mohammed (Dirasat: Human and Social Sciences, 2024)
Objectives: The study aims to shed light on the profound impact of the digital age on literature, its representation, and its impact in building a new identity for literature. It also explores the most important challenges undertaken by digital platforms that interested literature, after the tremendous development of technology has placed literature in front of abilities that no one imagined it would reach. Methods: The study relies on the data of the descriptive analytical method, which includes collecting texts and trying to analyze them in order to reach the desired goal of the study. Results:. The study finds that digital platforms release unleashed the positive and negative potentials of technology, and contribute to democratizing access to literature, especially for young generations, for whom digital culture has come to occupy an important part of their lives, with all the connotations and symbols it carries, rules of exchange and communication, and groups. Virtual, social relationships, etc. Conclusions: : The study concludes that the greatest challenge facing literary works in the age of digital platforms is allowing people of unknown parentage and teenagers to have open access to literature and write cheap and vulgar texts in the absence of serious electronic critical practice and experience so to speak.